Evidence for PAH Removal Coupled to the First Steps of Anaerobic Digestion in Sewage Sludge. (18th March 2013) - Cea-Barcia, Glenda; Carrère, Hélène; Steyer, Jean Philippe; Patureau, Dominique
Abstract : Anaerobic degradation of polycyclic aromatic hydrocarbons has been brought to the fore, but information on removal kinetics and anaerobic degrading bacteria is still lacking. In order to explore the organic micropollutants removal kinetics under anaerobic conditions in regard to the methane production kinetics, the removal rate of 12 polycyclic aromatic hydrocarbons was measured in two anaerobic batch reactors series fed with a highly loaded secondary sludge as growth substrate. The results underscore that organic micropollutants removal is coupled to the initial stages of anaerobic digestion (acidogenesis and acetogenesis). In addition, the organic micropollutants kinetics suggest that the main removal mechanisms of these hydrophobic compounds are biodegradation and/or sequestration depending on the compounds.